Increasing Students’ Vocabularies Through Flash card Strategy At Eight Grade Of SMP Negeri 3 Pulau-Pulai Babar, Southwest Maluku - Dian Sartin Tiwery (Journal on Education, 2023)
Flash card strategy as a strategy for increasing students' vocabulary skills at eight grades of SMP Negeri 3 Pulau-Pulau Babar. As one of the 3T areas, this school is limited in terms of infrastructure and teachers. Therefore, it is necessary to use the appropriate strategy to support students in their learning process. This research used classroom based research. The data were collected by field notes and interviews which are filled by students of the study. The findings of the study showed that most of the eight grade students at SMP Negeri 3 Pulau-Pulau Babar liked to use flash card strategy as their learning strategy in increasing vocabulary. Through this strategy, students seemed enjoy and enthusiastic as long as the process of teaching and learning English vocabulary in the classroom. So that they were easier in increasing their vocabulary mastery.